2012
DOI: 10.3382/ps.2011-01582
|View full text |Cite
|
Sign up to set email alerts
|

Effects of canthaxanthin on the productive and reproductive performance of broiler breeders

Abstract: The effects of supplementing canthaxanthin on productive and reproductive aspects of broiler breeders were examined in this study. In total, 360 female pullets and 36 roosters were placed in an open-sided house with 12 pens, each pen with an area of 7.0 m(2) (3.5 × 2.0 m). At 42 wk of age, the breeder hens and roosters were distributed into 2 experimental groups with similar BW and uniformity. From 46 to 66 wk of age, one group received 6 mg/kg of canthaxanthin supplemented in the diet and the other group rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 26 publications
4
40
0
1
Order By: Relevance
“…Their study demonstrated that dietary supplementation with canthaxantin caused a significant increase in the colourimetric value of egg yolk measured in the La'Roche scale. Investigations by Rosa et al (2012) with the use of canthaxantin (6 mg · kg -1 diet) as an additive in feed mixtures for laying hens proved that in the second week of supplementation, the colourimetric value of egg yolks increased from 9.33 to 14.67 pts in La'Roche scale. According to these authors, this difference in yolk colour remained stable over the entire 20-week experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Their study demonstrated that dietary supplementation with canthaxantin caused a significant increase in the colourimetric value of egg yolk measured in the La'Roche scale. Investigations by Rosa et al (2012) with the use of canthaxantin (6 mg · kg -1 diet) as an additive in feed mixtures for laying hens proved that in the second week of supplementation, the colourimetric value of egg yolks increased from 9.33 to 14.67 pts in La'Roche scale. According to these authors, this difference in yolk colour remained stable over the entire 20-week experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of canthaxanthin to the diet minimized the adverse effects of aging on the fertility of the roosters studied. ROSA et al (2012) found that the addition of canthaxanthin improves fertility and decreases embryonic mortality, resulting in increased hatchability. This effect has been attributed to reduced oxidant formation during the early stages of incubation and in stored eggs.…”
Section: ------------------------------------------Production Period mentioning
confidence: 99%
“…The reduction in mortality in the storage and initial incubation phases is related to reduced lipid peroxidation of egg components and of the embryo (ROSA et al, 2012). In the final stages of incubation, however, the increase in the metabolism of the embryo leads to higher oxygen consumption and increased lipid oxidation in the yolk to meet the energy requirements of the embryo (LATOUR et al, 2000).…”
Section: ------------------------------------------Production Period mentioning
confidence: 99%
See 1 more Smart Citation
“…Another experiment showing the role of CX in parental diet of chickens was conducted in Brazil (51). CX was found to reduce lipid peroxidation in yolks of stored incubation eggs laid by hens whose diet was supplemented with CX.…”
mentioning
confidence: 99%